Duration and determinants of Chagas latency: an etiology and risk systematic review protocol. (October 2019) - Henao-Martínez, Andrés F.; Chadalawada, Sindhu; Villamil-Gomez, Wilmer E.; DeSanto, Kristen; Rassi, Anis; Franco-Paredes, Carlos
ABSTRACT: Objective: The objective of this systematic review is to explore and discuss the latency duration among asymptomatic people with chronic Chagas disease. Introduction: Studies estimate the latency period of Chagas disease to be approximately 10–30 years. However, new findings may indicate that this latency period is shorter and depends on the presence of clinical factors. This systematic review protocol will explore the duration and factors affecting this latency period to inform treatment, with the potential of improving outcomes. Inclusion criteria: Eligible studies will include asymptomatic people with indeterminate Chagas disease confirmed through positive serologic testing and the absence of structural cardiomyopathy with no heart failure symptoms and normal electrocardiography results. Studies that involve a longitudinal observation period of participants will be considered. This period must start from the acute acquisition of the infection or an already established indeterminate form of the disease until the development of a primary or secondary cardiac outcome. Methods: The following electronic databases will be searched: MEDLINE, Embase, Cochrane Library, Web of Science Core Collection and LILACS. The search will include the following concepts: Chagas disease, latency duration and determinants of the Chagas latency period. The languages will be restricted to English, Spanish and Portuguese. Two reviewers will review the selected studies for methodological quality using critical appraisal tools and conduct data extraction. Studies will, where possible, be pooled in a statistical meta-analysis. All data will be presented and synthesized through tables, summaries, figures and charts. Systematic review registration number: PROSPERO CRD42019118019